2011
DOI: 10.1097/aog.0b013e318209d669
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol Vaginal Insert for Successful Labor Induction

Abstract: ClinicalTrials.gov, www.clinicaltrials.gov, NCT00828711.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 13 publications
2
30
2
2
Order By: Relevance
“…The period from the beginning of labor induction to amniotic fluid rupture was shorter in misoprostol group. In previous studies, including large meta-analysis, the results were similar to those shown below [8]. Nevertheless, it should be noted that in the literature comparisons of exact these two types of prostaglandin administration are not available.…”
Section: Discussionsupporting
confidence: 72%
“…The period from the beginning of labor induction to amniotic fluid rupture was shorter in misoprostol group. In previous studies, including large meta-analysis, the results were similar to those shown below [8]. Nevertheless, it should be noted that in the literature comparisons of exact these two types of prostaglandin administration are not available.…”
Section: Discussionsupporting
confidence: 72%
“…Yet, we observed this rate to be relatively higher in the primigravida group (40.58% vs. 16.13%) and in the group with concomitant preeclampsia or diabetes. However, other authors report the caesarean section rate after pre-induction with MVI to be even lower -from 22.9% to 27.1% [19,24]. Similarly to other studies, we report the risk of intrauterine fetal hypoxia to be the most common indication for a caesarean section [3,15,24].…”
Section: %mentioning
confidence: 46%
“…In our study we recorded only 2% of cases with tachysystoly, same for hyperstimulation. This is a very low proportion compared to literature, where such rate was reported to reach 13% to 53% of pregnancies [3,15,16,19]. Abnormalities of cardiotocographic tracing were recorded in 43% of cases but less than half of them required caesarean section.…”
Section: %mentioning
confidence: 50%
See 1 more Smart Citation
“…2 In another Cochrane review quoted by Bernardes et al in support of their main finding, Wood et al pointed out that their meta-analysis was heavily influenced by the Canadian Post Dates Trial, where cervical ripening with intracervical prostaglandin E was only planned in the immediate induction group (51% of the women in this group), and was discouraged in the expectantly managed (EM) group (9%). 3,4 In the study conducted by Bernardes et al, 96.3% of women in the induction group benefitted from timely cervical ripening with intracervical or intravaginal prostaglandins or a balloon catheter, versus 'only' 48% of women in the EM group. Of note, the proportion of women who received local prostaglandins or balloon catheter in the EM group of the study by Bernardes et al was similar to the induction group in the Canadian Post Dates Trial, in line with a very active policy of cervical ripening that probably explains the low caesarean rate in the DIGITAT and HYPITAT studies.…”
mentioning
confidence: 99%